1976
DOI: 10.1017/s0016756800042990
|View full text |Cite
|
Sign up to set email alerts
|

Reinterpretation of ceratitic ammonoids from the Greville Formation, New Zealand

Abstract: SummaryCeratitic ammonoids from the Greville Formation in the Nelson Regional Syncline, South Island of New Zealand, were described as a new genus and species of the Ophiceratidae, Durvilleoceras woodmani, and dated as ‘late Middle Permian’ (Waterhouse, 1973). In fact, Durvilleoceras differs from all known Permian ammonoids in both conch form and sutural pattern, but closely resembles lower Triassic ceratites. Structural and sedimentologic complexities within the Nelson Syncline are such that stratigraphic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 3 publications
(7 reference statements)
0
21
0
Order By: Relevance
“…A late Middle Permian age for the ammonite species was suggested by Waterhouse (1973Waterhouse ( , 1979 based mainly on the stratigraphic evidence that the overlying Stephens Formation in Nelson contains a well-established Late Permian fauna. Furnish et al (1976) noted that the morphology of the ammonite differs from all known Permian forms but closely resembles those of Early Triassic age. The discovery of a later Late Permian fauna within the Stephens Formation (sensu lata) at Mossburn by Hyden et al (1982) appears to further enhance the arguments of Waterhouse (1973Waterhouse ( , 1979.…”
Section: Discussion Of Agementioning
confidence: 93%
See 1 more Smart Citation
“…A late Middle Permian age for the ammonite species was suggested by Waterhouse (1973Waterhouse ( , 1979 based mainly on the stratigraphic evidence that the overlying Stephens Formation in Nelson contains a well-established Late Permian fauna. Furnish et al (1976) noted that the morphology of the ammonite differs from all known Permian forms but closely resembles those of Early Triassic age. The discovery of a later Late Permian fauna within the Stephens Formation (sensu lata) at Mossburn by Hyden et al (1982) appears to further enhance the arguments of Waterhouse (1973Waterhouse ( , 1979.…”
Section: Discussion Of Agementioning
confidence: 93%
“…), and they provide a direct age for the formation. Unfortunately, their generic affinities and hence biostratigraphic significance are disputed (Furnish et al 1976;Waterhouse 1979). A late Middle Permian age for the ammonite species was suggested by Waterhouse (1973Waterhouse ( , 1979 based mainly on the stratigraphic evidence that the overlying Stephens Formation in Nelson contains a well-established Late Permian fauna.…”
Section: Discussion Of Agementioning
confidence: 99%
“…The age of Durvilleoceras woodmani has been variously interpreted as Late Permian (e.g., Waterhouse 1964bWaterhouse , 1979Waterhouse , 1987Johnston & Stevens 1978;Pillai et al 1991), Early Triassic (Furnish et al 1976;Owen 1995), and Middle Triassic (Waterhouse 1993). Owen (1995) also recorded an Early Triassic evolute xenodiscid ammonoid from the Greville Formation in Nelson.…”
Section: Age Of Maitai Group Strata At West Domementioning
confidence: 99%
“…Waterhouse (1973aWaterhouse ( , 1979Waterhouse ( , 1987 claimed a Late Permian age for D. woodmani, and later suggested a middle Triassic (Anisian) age (Waterhouse 1993). Based on the similarity of D. woodmani to Early Triassic Flemingitidae, Furnish et al (1976) suggested a mid-Early Triassic (Dienerian-Smithian) age. Johnston & Stevens (1978) described two ammonoids {lEpisagiceras aff.…”
Section: Greville Formationmentioning
confidence: 99%